2018
DOI: 10.1155/2018/3274641
|View full text |Cite
|
Sign up to set email alerts
|

miR-142-5p in Bone Marrow-Derived Mesenchymal Stem Cells Promotes Osteoporosis Involving Targeting Adhesion Molecule VCAM-1 and Inhibiting Cell Migration

Abstract: Osteoporosis is a systemic bone metabolic disease that is highly prevalent in the elderly population, particularly in postmenopausal women, which results in enhanced bone fragility and an increased susceptibility to fractures. However, the underlying molecular pathogenesis mechanisms still remain to be further elucidated. In this study, in a rat ovariectomy- (OVX-) induced postmenopausal osteoporosis model, aberrant expression of a microRNA miR-142-5p and vascular cell adhesion molecule 1 (VCAM-1) was found by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…miRNAs also regulate the differentiation of mesenchymal stem cells and osteoblasts (19,20). During the processes of bone differentiation and regeneration, abnormal miRNA expression is closely associated with OP (21,22). For example, the miR-34c-induced silencing of MC3T3-E1 reduces the inhibitory effect of vaspin on osteoblast differentiation (23); furthermore, miRNA (miR)-433-3p can regulate osteoblastic differentiation by targeting Dickkopf-1 ( DKK1 ) (24).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs also regulate the differentiation of mesenchymal stem cells and osteoblasts (19,20). During the processes of bone differentiation and regeneration, abnormal miRNA expression is closely associated with OP (21,22). For example, the miR-34c-induced silencing of MC3T3-E1 reduces the inhibitory effect of vaspin on osteoblast differentiation (23); furthermore, miRNA (miR)-433-3p can regulate osteoblastic differentiation by targeting Dickkopf-1 ( DKK1 ) (24).…”
Section: Introductionmentioning
confidence: 99%
“…As a postmenopausal osteoporosis disease model Teng et al . [ 19 ] analyzed a total miRNA expression analysis in bone marrow derived mesenchymal stem cells of mice with oophorectomy. In all miRNAs , the expression level of miR-142-5p increased the most compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…VCAM1 was decreased in HEK293T cells, as revealed by luciferase assay. VCAM-1 has an important role in cell-cell recognition, inflammation, development of various organs and formation of immune responses and is also involved in the activation and migration of immune cells [ 19 ]. The increased expression of miR-142-5p and reduced expression of VCAM-1 demonstrated in the osteoporosis model by Teng et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, our results also provide a potential link between miR-142-5p and the self-renewal ability of ESCC cells where exogenous miR-142-5p led to a decreased ability to generate tumor spheres in both OE21 and OE33 cells. A recent study indicated that miR-142-5p functioned to suppress cell migration by targeting VCAM-1 in bone marrow-derived mesenchymal stem cells [40]. Trisaal et al showed that loss-of-function the in miR-142 gene resulted in the increase in HOXA gene (a key gene for maintaining stemness in hematopoietic stem cells) and promoted leukemogenesis [41].…”
Section: Discussionmentioning
confidence: 99%